2016
DOI: 10.1371/journal.pone.0156412
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 Polymorphisms Contribute to Intervertebral Disc Degeneration Risk: A Meta-Analysis

Abstract: ObjectiveWe performed a meta-analysis to assess association between interleukin 1 (IL-1) polymorphisms and the risk of Intervertebral Disc Degeneration (IDD).BackgroundA series of studies have investigated the association between common single nucleotide polymorphisms in IL-1 and IDD risk; however, the overall results are inconclusive.MethodsTwo independent investigators conducted a systematic search for relevant available studies. Allele frequencies were extracted from each study. The association between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…It is often exposed to an inflammatory microenvironment. IL-1 β , a proinflammatory cytokine involved in inflammatory processes and the induction of apoptosis in response to cell injury, has been reported to have a connection with the degeneration of intervertebral discs [ 3 ]. Low back pain (LBP) is a frequent musculoskeletal disorder worldwide that affects approximately 70% of the adult population, sometime during their lives, and frequently results in musculoskeletal disability.…”
Section: Introductionmentioning
confidence: 99%
“…It is often exposed to an inflammatory microenvironment. IL-1 β , a proinflammatory cytokine involved in inflammatory processes and the induction of apoptosis in response to cell injury, has been reported to have a connection with the degeneration of intervertebral discs [ 3 ]. Low back pain (LBP) is a frequent musculoskeletal disorder worldwide that affects approximately 70% of the adult population, sometime during their lives, and frequently results in musculoskeletal disability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of qRT-PCR and IHC analysis demonstrated that increased IL-1α and IL1-β expression levels were found in the degenerated disc. Wang et al initially reported a metaanalysis on IL-1α rs1800587 and IL-1β rs1143634 polymorphisms and LDD, which suggested that IL-1α rs1800587 polymorphism was signi cantly associated with the risk of disc degeneration [29]. There were several weaknesses in the previous meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in these genes were associated with susceptibility to other human diseases. The IL-1 gene cluster is located on chromosome 2q13–2q14.1 and is comprised of nine genes: IL-1α , IL-1β , the IL-1 receptor antagonist (IL-1RN) , and six IL-1-like factor genes ( IL-1F5 through IL-1F10 ) [ 31 ]. IL-1β is in a 70–110 kb region of chromosome 2q13–21 and consists of 7 exons and 6 introns [ 32 ].…”
Section: Discussionmentioning
confidence: 99%